Effect of Magnetic Treatment of water for irrigation and seed Qualities of the Plant vegetative growth corundum oriandrum sativum of - Baghdad Science Journal (مجلة بغداد للعلوم)
Cultured fruits of theCorundum Coriandrum sativum were sown On 11/11 / 2008 in basins containing 15 kg of soil (Silty Loam) .Fruits were divided into two parts the first was soaked in normanl water and the second was magnetized for a period of 24 hours Irrigation was up to (75% of capacity field.Two types of water (normal water and magnetized water)with three repetitions were used the access to magnetic water was supplied from a special electric device. Recorded measurements were plant height the number of stems / plant, weight of plant, number of flowers, 1000 seed weight) during the cultivation period, which ended on 11/5/2009. Results indicated the absence of any effect of magnetic water on plant growth of Fenugreek while seeds treated with a magnetic water showed significantly different characteristics.